Phymaturus Palluma (High Mountain Lizard) diet - Vicenzi, Nadia Pamela (2018)
Phymaturus palluma is a medium-sized, saxicolous, viviparous, and herbivorous lizard that inhabits the Altoandina phytogeographic province in the Andes Highlands, Argentina. Populations are restricted to rocky outcrops, and their diet is based on shrub vegetation like Artemisia and Ephedra (Videla 1983. Deserta 7:192? 202). During October 2014 (austral spring), we observed and recorded individuals of P. palluma eating small bites of soil and licking rocks (Fig. 1) at the Aconcagua Provincial Park, Mendoza, Argentina.